Hubungan Tingkat Kepatuhan Pasien pada Penggunaan Obat Antidiabetes terhadap Kadar Glukosa Darah di Puskesmas X Indramayu - Tuti Awaliyah A; Rosdaniati Rosdaniati; Haqoiroh Haqoiroh (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Diabetes mellitus (DM) is a global public health threat, and around 90% of all patients suffering from DM throughout the world are type 2 DM. Non-compliance related to Diabetes Mellitus is something that is a problem that should be avoided. This study aims to determine the level of patient compliance with the use of antidiabetic drugs at the Cidemp Indramayu Community Health Center, and to determine the relationship between the level of compliance of Diabetes Mellitus patients with blood glucose levels (fasting and while) at the Cidemp Indramayu Community Health Center. This research is a type of analytical observational research with a research design. cross-sectional. Data analysis in this study used SPSS version 23 software. The results showed that the majority of respondents fell into the